1971
DOI: 10.1055/s-0038-1654330
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of Fibrinogen and Its Degradation Products by Basic Proteins

Abstract: SummaryFibrinogen and early fibrinogen degradation products (FDP) of plasmin digestion containing Fragment XfP gave highly ordered polymers of limited branching with protamines and synthetic polylysine (molecular weight 175,000). Histones, polylysine of molecular weight 2,500, granulocyte cationic protein and platelet factor 4 formed amorphous precipitates with fibrinogen and early FDP. Fibrin degradation products (fdp) containing complexes of Fragment X° formed highly ordered polymers of extensive branching w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1972
1972
2011
2011

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 22 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…One of the major histone‐interacting plasma proteins was fibrinogen, which is known to precipitate following the addition of histones 20. An electron microscopic study showed that histone–fibrinogen co‐precipitates took the form of globules, clumps or rudimentary fibrils, dependent on the histone fractions used 28. Gonias et al found that histone H3 caused a concentration dependent increase in fibrinogen precipitation 20.…”
Section: Discussionmentioning
confidence: 99%
“…One of the major histone‐interacting plasma proteins was fibrinogen, which is known to precipitate following the addition of histones 20. An electron microscopic study showed that histone–fibrinogen co‐precipitates took the form of globules, clumps or rudimentary fibrils, dependent on the histone fractions used 28. Gonias et al found that histone H3 caused a concentration dependent increase in fibrinogen precipitation 20.…”
Section: Discussionmentioning
confidence: 99%
“…76 Electron microscopy suggested that some aggregates of histones with fibrinogen or fibrin were rudimentary fibrils. 77 Furthermore, during inflammatory responses to sepsis, neutrophils actively make neutrophil extracellular traps (NETs) that associate with bacterial pathogens, and contain DNA and the four core histones. 78 Interestingly, these fibrous structures have a diameter of $15 nm, about twice the diameter of fibrils formed by calf thymus histones.…”
mentioning
confidence: 99%